Pemanfatan Limbah Tongkol Jagung Sebagai Bahan Pembuatan Bangke, Kudapan Kaya Serat dan Protein - Widiati, Bibiana Rini; Haerul, Haerul; Sadat, Moh. Anwar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
The potential of corn cob waste, which has low-calorie characteristics and is rich in fiber, can be processed into an alternative fiber- and protein-rich snack. The purpose of this community service activity is to utilize corn cob waste as an effort to diversify food and improve the skills of partners in processing corn cob waste into